Spontaneous Labor Onset and Outcomes in Obese Women at Term - Frolova, Antonina I.; Wang, Judy J.; Conner, Shayna N.; Tuuli, Methodius G.; Macones, George A.; Woolfolk, Candice L.; Cahill, Alison G. (American Journal of Perinatology, 2018)
Objective The objective of this study was to compare the rates of spontaneous labor onset and its progression in obese and nonobese women after 37 weeks.Study Design We performed a secondary analysis of a retrospective cohort of all women who were admitted for delivery at ≥ 37 weeks of gestation at a university-based tertiary care center between 2004 and 2010. The cohort was stratified by weeks of gestation at which the patient presented for delivery. The rates of spontaneous labor, vaginal delivery, and augmentation with oxytocin were compared between obese (body mass index [BMI] ≥ 30) and nonobese (BMI < 30) women.Results Obese women had lower rates of spontaneous labor than nonobese women at every gestational week (37 weeks, 6.1 vs. 9.3%, p < 0.001; 38 weeks, 12.8 vs. 19.2%, p < 0.001; 39 weeks 26.0 vs. 37.0%, p < 0.001; 40 weeks, 39.6 vs. 50.2%, p < 0.001; 41 weeks, 30.8 vs. 38.0%, p < 0.012). Among women who presented in spontaneous labor, obesity was associated with higher rates of augmentation with oxytocin and lower rates of vaginal delivery.Conclusion Obese women at or beyond 37 weeks are less likely to experience spontaneous labor compared with nonobese women. In addition, obese women presenting in spontaneous labor are less likely that nonobese women to have a vaginal delivery at 37 to 40 weeks, even after oxytocin augmentation.
Keywords: obesity; spontaneous labor; labor augmentation; parturition